Epidemiology of diagnosed cluster headache in Norway. (7th February 2022) - Crespi, Joan; Gulati, Sasha; Salvesen, Øyvind; Bratbak, Daniel Fossum; Dodick, David W; Matharu, Manjit Singh; Tronvik, Erling
Background: Cluster headache (CH) is one of the most painful conditions in humans and there is limited epidemiological data on this debilitating condition. Objectives: To describe the epidemiology of CH in Norway Methods: We conducted a nationwide study to investigate the prevalence, incidence, and comorbidity of CH in Norway between January 1 2008 and December 31 2016. Treatment and outcome data from the Norwegian patient registry and the Norwegian prescription database were linked on an individual basis. Results: Among 3, 892, 260 individuals ≥18 years old of age, we identified a total of 1891 patients with CH. The prevalence of CH was 48.6 per 100, 000, and the male-to-female ratio was 1.47. The estimated incidence of CH was 3.0 per 100, 000/year. Among patients with CH, increased age and sex adjusted odds ratios ([OR], all with p -values <0.0001, were observed for medication-induced headache (OR 50.7, 95% CI 36.7–69.9), migraine (OR 25.2, 95% CI 22.5–28.3), chronic posttraumatic headache (OR 22.2, 95% CI 12.8–38.45), history of cranial trauma (OR 1.9, 95% CI 1.5–2.4), somatoform disorders (OR 4.2, 95% CI 3.0–5.8), suicide attempt (OR 3.9, 95% CI 2.6–5.8), personality disorder (OR 3.6, 95% CI 2.6–4.9), bipolar disorder (OR 3.6, 95% CI 2.8–4.8), peptic ulcer (OR 2.8, 95% CI 2.3–3.3), depression (OR 2.8, 95% CI 2.4–3.1), substance abuse (OR 2.6, 95% CI 2.0–3.3), and cerebrovascular disease (OR 2.4, 95% CI 1.8–3.1). Use of opioid analgesics during the study period was more common among patients with CH compared to others (81% vs. 22%, sex and age adjusted OR 23.4, 95% CI 20.8–26.2, p < 0.0001).